Gambaran Faktor Konsumsi Tablet Tambah Darah Pada Remaja Putri - Susi Irianti; Sahiroh Sahiroh (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2019)
Teenagers are periods that are considered vulnerable from a nutritional perspective for several reasons. First, in terms of increasing the need for nutrients because of physical growth and rapid development. One of the problems of nutrition and health of young women is anemia. The purpose of this study was to determine the picture of the factors that consume blood-added tablets in Class VIII female adolescents in junior high school 1 Ciruas in 2019. The type of research was descriptive, the simple random sampling technique was 100 respondents. The results of the study of young women who consumed tablets plus 80 people 80%, and, positive attitudes 87 people (87%), received teacher support 69 people (69%), received support from parents of 73 people (73%). Keywords:Anemia, Fe, Blood Added Tablets ABSTRAK Remaja adalah periode yang dianggap rentan dari sudut pandang gizi karena beberapa alasan. Pertama, dari sisi bertambahnya kebutuhan zat gizi karena pertumbuhan dan perkembangan fisik yang sangat cepat. Salah satu masalah gizi dan kesehatan remaja putri adalah anemia. Tujuan penelitian ini untuk mengetahui gambaran faktor konsumsi tablet tambah darah pada remaja putri kelas VIII di SMP Negri 1 Ciruas Tahun 2019. Jenis Penelitian deskriptif, teknik pengambilan sampel simple random sampling sebanyak 100 responden. Hasil penelitian remaja putri yang konsumsi tablet tambah darah 80 orangg 80%, dan, sikap positif 87 orang (87%), mendapatkan dukungan guru 69 orang (69%), mendapatkan dukungan orang tua 73 orang (73%). Kata Kunci: Anemia, Fe, Tablet Tambah Darah